X-6 / 4 - 2x + 1 / 2 -3 = x / 3-1 / 2 어떻게 풀리나요?

X-6 / 4 - 2x + 1 / 2 -3 = x / 3-1 / 2 어떻게 풀리나요?
Anonim

대답:

#x = -21 / 8 #

설명:

#x -6/4 - 2x + 1 / 2 - 3 = x / 3 - 1 / 2 #

#x -3/2 - 2x + 1 / 2 - 3 = x / 3 - 1 / 2 #

# (x-2x) + (-3/2 + 1 / 3) = x / 3 - 1 /

# (- x) + (- 1 - 3) = x / 3 - 1 / 2 #

# (- x) + (- 4) = x / 3 - 1 / 2 #

# -x - 4 + (-x / 3) = x / 3 - 1/2 + (-x / 3) #

# - (1 1/3) x - 4 = - 1/2 #

# - (1 1/3) x - 4 + (4) = - 1 / 2 + (4) #

# - (1 1/3) x = 3 1 / 2 #

# -4 / 3x = 7 / 2 #

# -4 / 3 * (3/4) x = 7 / 2 * (3/4) #

# - x = 21 / 8 #

# - x * (- 1) = 21/8 * (- 1) #

#x = -21 / 8 #

Lo siento, mi Espan ~ ol 아니오 esta 'bueno. 요 에스코 데스 에이스.